2014
DOI: 10.1039/c4ra10685g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of Zn2+/Cd2+-directed self-assembled metallo-supramolecular polymers based on 1,4-diketo-pyrrolo[3,4-c]pyrrole (DPP) derivatives

Abstract: New building blocks based on 1,4-diketopyrrolo [3,4-c]pyrrole (DPP), 2,5-bis(2-ethylhexyl)-3,6-bis(5-[p-(2,2':6 0 ,2 00 -terpyridine-4 0 -yl) phenyl]thiophen-2-yl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione (M1) and 2,5bis(2-ethylhexyl)-3,6-bis(4-[p-(2,2 0 :6 0 ,2 00 -terpyridine-4 0 -yl) phenyl]phenyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione (M2) were synthesized by the Suzuki Pd-catalyzed cross-coupling reaction. Under moderate conditions, directed self-assembly polymerizations by the transition metal ions Zn 2+ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…PhDPP, TDPP, and palladium octabutoxy­phthalocyanine (PdPc) were synthesized and purified according to reported literature procedures. , PhTDPP was synthesized from 3,6-bis­(5-bromo­thien-2-yl)-2,5-bis­(2-ethyl­hexyl)-DPP as described below. Phenylboronic acid was purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…PhDPP, TDPP, and palladium octabutoxy­phthalocyanine (PdPc) were synthesized and purified according to reported literature procedures. , PhTDPP was synthesized from 3,6-bis­(5-bromo­thien-2-yl)-2,5-bis­(2-ethyl­hexyl)-DPP as described below. Phenylboronic acid was purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Superior PV properties are generally expected for solar cells based on such metallosupramolecular polymers. 48 Conjugated polymers containing Fig. 7 The TEM images of PDPCz21/PC 71 BM blend solid films after annealing at 100 C for 10 min.…”
Section: Morphologies Of Pt/pc 71 Bm-based Thin Lmsmentioning
confidence: 99%
“…For example, Qiu et al reported an asymmetric thiophene/pyridine-anked DPP polymer (PyTDPP) that exhibited a narrow band gap, a wide light absorption range, and a relatively deep HOMO; PyTDPP-based PVCs displayed high PV efficiency. 47 Furthermore, Chen et al synthesized two terpyridine-functionalized DPP derivatives; 48 directed by zinc(II) and cadmium(II) ions, these DPP derivatives underwent polymerization to form metallo-supramolecular polymers, which exhibited low band gap energies (1.51-1.58 eV) and broad absorption bands (ranging from ca. 300 to 800 nm), suggesting potential applications in high-performance PV materials.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of this strategy toward functional supramolecular materials has been reported by Chen and co-workers. In this work, the authors utilized a terpyridine-containing DPP derivative to generate supramolecular polymers through the coordination of Zn­(II) and Cd­(II) . Similar to the previous example, J-type aggregation was observed in these supramolecular materials, resulting in particular interesting chromophoric and physical properties.…”
Section: Introductionmentioning
confidence: 99%